Book Review âMagnet Wealth & Success (Malay Version) - Alam, Shah (Social Science Learning Education Journal, 2017)
Written by Azizan Osman, this Magnet Wealth & Success book is the basic essence of suction to his intensive training program, which he founded in 2009. It is a 4-day seminar program called Intensive Magnet Wealth & Success (Previously known as Intensive Mentor Wealth & Success), which has helped transform the lives of hundreds of thousands of participants present. This book hopes to helps readers to transform their thoughts and feelings to be a magnet to all the good to achieve the dream of living a happier, healthier, rich, successful and hopefully blessed by Allah SWT. Whatever the formula that the author shared a formula proven to him and those who have used it vigorously and unusual. It is the result of his own experience from a writer who had been through dark age in the business and investment some time ago that he found light in the course of his life transformation. The light is knowledge is being acquired by learning from the mistakes themselves as well as the results of those who have studied with proven success in their field.